2022
DOI: 10.1088/1755-1315/1027/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of plant species in the proboscis monkey’s habitat as a species reference for habitat restoration

Abstract: Most of the Proboscis monkey (Nasalis larvatus) habitat is outside the protected area, so the potential for destruction is high. One of the efforts to improve its habitat is habitat restoration. This study aims to determine plant species for proboscis monkey habitat restoration based on reference habitats. The research was conducted at eight locations in East Kalimantan, Indonesia i.e. Kuala Samboja, Mahakam Delta, Suwi River, Ohong River, Berau Delta (mangrove and riverine), Sungai Wain, and Kutai National Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…This discovery is assumed to be proboscis monkey bite marks, given that leaves are the primate's primary food source (folivorous) (Boonratana, 1993). Other mangrove species on Balikpapan Bay reported to have a high preference as a food source for proboscis monkeys are R. apiculata (Tangah & Bernard, 2010), S. alba, and S. caseolaris (Atmoko, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discovery is assumed to be proboscis monkey bite marks, given that leaves are the primate's primary food source (folivorous) (Boonratana, 1993). Other mangrove species on Balikpapan Bay reported to have a high preference as a food source for proboscis monkeys are R. apiculata (Tangah & Bernard, 2010), S. alba, and S. caseolaris (Atmoko, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mangrove vegetation has a strong interaction with the presence of proboscis monkeys because the monkeys like young leaves, seeds, and mangrove fruit as food sources (Boonratana, 1993). Atmoko (2022) has reported as many as 41 plant species as food sources for proboscis monkeys from several habitats in East Kalimantan. In addition, proboscis monkeys often choose large mangrove trees on the banks of rivers or seas as sleeping trees to avoid predators.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wakushima et al (1994) showed that S. alba grows in soil with high salinity and high pH and B. gymnorrhiza in soil exhibiting varying pH levels. S. alba has been reported to be a high preference plant for proboscis monkey food resource selection (Atmoko et al 2022). However, additional research in the future is required to understand the specific correlation of pH on resource selection of the proboscis monkey.…”
Section: Discussionmentioning
confidence: 99%